Multiomics analyses of human colorectal cancer reveal changes in mitochondrial metabolism associated with chemotherapy resistance - Chen, Shiyi; Li, Qian; Zheng, Wei (Frontiers in Oncology, 2025)
BackgroundMitochondria are essential organelles involved in energy production, cellular metabolism, and signal transduction. They have important impacts on tumorigenesis and cancer progression. Nevertheless, the associations between mitochondrial metabolic processes and chemotherapy resistance in colorectal cancer (CRC) are not well understood.MethodsWe generated a chemotherapy-resistant colorectal cancer cell line, HCT-15/DOX, via doxorubicin (DOX) induction. We then performed proteomic and metabolomic analyses via LC-MS/MS technology on both the parental and the DOX-resistant cell lines. Additionally, transmission electron microscopy was used to examine changes in mitochondrial morphology between the two cell lines.ResultsThe results revealed significant dysregulation of 185 proteins and 1099 metabolites in HCT-15/DOX cells relative to parental cells, highlighting the impact of chemotherapy resistance on cellular processes. The key functional proteins that were identified included upregulated SDHA, BCKDHB, CRYZ, NUDT6, CPT1A, and POLG, and downregulated CRAT, FDPS, SFXN1, and ATAD3B. Additionally, through combined multiomics pathway enrichment analysis, pyrimidine metabolism, purine metabolism, ascorbate and aldarate metabolism, propanoate metabolism, and the citrate cycle (TCA cycle) were identified as important metabolic processes associated with CRC chemotherapy resistance. Transmission electron microscopy analysis revealed that HCT-15/DOX cells had increased mitochondrial number, length, and area.ConclusionsThis research highlights notable differences in mitochondrial morphology and diverse mitochondrial metabolic functions between parental and DOX-resistant HCT-15 CRC cells. The findings of the present study provide insights into the mitochondrial metabolic changes associated with CRC chemotherapy resistance, offering valuable insights into the mechanisms underlying these changes and identifying potential therapeutic targets for addressing CRC chemotherapy resistance.